Peluang dan Tantangan Penyandang Disabilitas Dalam Dunia Kerja (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
The position of humans in the eyes of God is considered equal, but often it is humans themselves who create differences in treatment towards fellow humans. This differential treatment is particularly felt by individuals with physical, mental, or intellectual limitations, known as people with disabilities. Disability is defined as a condition in which someone experiences long-term physical, intellectual, mental, and/or sensory limitations, resulting in obstacles and difficulties in social interaction. This article discusses the challenges and opportunities faced by people with disabilities in the workplace, as well as the government's role in creating inclusive employment opportunities and laws that protect their rights in the workplace. Despite the existence of many laws regulating this matter, people with disabilities often still face discrimination in the workplace. The method used in writing this article is through literature review, involving understanding and learning theories relevant to the topic.